Analysing the impacts of a large-scale EV rollout in the UK – How can we better inform environmental and climate policy?. (July 2020) - Calvillo, Christian F.; Turner, Karen
Abstract: Electrifying transport to meet local pollution and overall net zero carbon ambitions is now a key UK policy focus, but this will have important impacts on the energy system, the economy, and the environment. Understanding the changes that the electrification of transport will bring is crucial for developing sustainable policies for net zero goals and a just transition. A literature is emerging to analyse the impact of a large-scale penetration of electric vehicles (EVs), but generally limiting focus to the implications for the electricity network. In this paper, we aim to provide insight on the wider energy system impacts of the expected EV rollout in the UK, in terms of fuel changes, energy costs, CO2 emission reduction and network investments; and how different EV charging strategies increase or mitigate the impacts of the expected large-scale penetration of EVs. Results show that non-smart and/or decentralised charging will require considerably larger investments on the network to accommodate new EV demand. Network reinforcement costs are passed to the consumer via increased electricity prices and, albeit reduced, emissions shift from the transport to the power sector. These results show the importance of considering the whole energy system and the wider economy, to avoid carbon leakage and to maximise the effectiveness of policies. Highlights: We provide insight on the energy system impacts of the expected EV rollout in the UK. Available literature generally only focuses on implications for the electricity network. We analyse impacts in terms of fuel use, energy costs, CO2 emissions and network investments. We analyse how different EV charging strategies increase or mitigate these impacts.